2013
DOI: 10.1002/ajmg.a.35921
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of a region responsible for panhypopituitarism in 20p11.2

Abstract: We report on the case of a young woman with a de novo 20p11.21p11.23 deletion, discovered by array-CGH. She has behavioral troubles with autistic traits, intellectual disability, panhypopituitarism, severe hypoglycemia, epilepsy, and scoliosis. The majority of the reported 20p deletions are located on the 20p12 region, covering the JAG1 gene responsible for the Alagille syndrome. More proximal deletions are even rarer, with very few cases described in the literature to date. The deletion carried by our patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Heterotaxy has been reported in at least three other patients with 20p11.2 deletions that include FOXA2 (Kale et al, ; Tsai et al, ) and is not reported in patients where FOXA2 is not deleted (Figure b, Kamath 2009 Pt 19 and Pt 21; Table SII). Other midline defects most frequently described were structural or functional pituitary anomalies (e.g., panhypopituitarism), seen in 5 of the 7 previously reported patients in whom this feature was specified (Table SI) (Dayem‐Quere et al, ; Garcia‐Heras et al, ; Kale et al, ; Kamath et al, ; Williams et al, ). Additional midline defects include a paramedian cleft lip and palate reported in one patient with a 20p11.2 deletion (Williams et al, ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Heterotaxy has been reported in at least three other patients with 20p11.2 deletions that include FOXA2 (Kale et al, ; Tsai et al, ) and is not reported in patients where FOXA2 is not deleted (Figure b, Kamath 2009 Pt 19 and Pt 21; Table SII). Other midline defects most frequently described were structural or functional pituitary anomalies (e.g., panhypopituitarism), seen in 5 of the 7 previously reported patients in whom this feature was specified (Table SI) (Dayem‐Quere et al, ; Garcia‐Heras et al, ; Kale et al, ; Kamath et al, ; Williams et al, ). Additional midline defects include a paramedian cleft lip and palate reported in one patient with a 20p11.2 deletion (Williams et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Additional midline defects include a paramedian cleft lip and palate reported in one patient with a 20p11.2 deletion (Williams et al, ). Dayem‐Quere and colleagues proposed a region of approximately 1.35 Mb ([GRCh37] chr20:22,303,261‐23,652,145) that includes FOXA2 as the critical region associated with hypopituitarism and/or growth hormone deficiency (Dayem‐Quere et al, ). Based on a 277 kb deletion of 20p11.21 ([GRCh37] chr20:22,496,147‐22,773,103) encompassing only FOXA2 and two long intergenic non‐coding RNAs in a patient with biliary atresia, interrupted inferior vena cava, and abdominal heterotaxy; it was proposed that FOXA2 alone is responsible for heterotaxy and panhypopituitarism (Tsai et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximal deletions of 20p11 are rare. Four patients with 20p deletions of varying sizes, which include FOXA2 have been previously reported in the literature [Garcia‐Heras et al., ; Kamath et al., ; Williams et al., ; Dayem‐Quere et al., ], and their reported symptoms include intellectual disability, developmental delay, seizures, panhypopituitarism, and facial dysmorphism [Dayem‐Quere et al., ]. Three of the four patients had panhypopituitarism while the remaining patient had an empty sella and presented with growth hormone deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…At least two case reports of CH can be retrieved in the literature. One article describes panhypopituitarism in a young woman [24] , while the other article describes a young man with GH and TSH deficiency [25] . Very recently Italian researchers wished to verify the involvement of JAG1 variants in the pathogenesis of congenital thyroid defects and the frequency of unexplained hypothyroidism in a series of ALGS1 patients (n = 21) and 100 unrelated patients with congenital hypothyroidism (controls) [26] .…”
Section: Resultsmentioning
confidence: 99%